Re-Orientasi Kurikulum Pendidikan Islam - Manpan Drajat (al-Afkar, Journal For Islamic Studies, 2020)
The development of science and technology is so fast. This development has an impact on the social fabric of society. This certainly must be responded by education in order to adapt to the development of these changes including Islamic religious education. Islamic education must be able to adapt to the changing times. One of the important things in education is the curriculum. Therefore, there is a need for curriculum reorientation in the context of adaptation to changes and developments in this era. This research uses a qualitative approach with the method of literature study. Curriculum components that need to be reoriented are educational goals, learning methods and approaches, contextual material and authentic assessment. This curriculum reorientation needs to be implemented to meet the needs of Islamic education of children who are able to adapt to the times.